Cover, Table of Contents, and Editorial Note – Vol. 15 No. 1 (2026) - Alief Budiyono (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Cover, Table of Contents, and Editorial Note – Vol. 15 No. 1 (2026)